Back to Basics: Adherence With Guidelines for Glucose and Temperature Control in an American Comprehensive Stroke Center Sample. Issue 3 (June 2018) - Alexandrov, Anne W.; Palazzo, Paola; Biby, Sharon; Doerr, Abbigayle; Dusenbury, Wendy; Young, Rhonda; Lindstrom, Anne; Grove, Mary; Tsivgoulis, Georgios; Middleton, Sandy; Alexandrov, Andrei V.
Abstract : ABSTRACT: Background: Variance from guideline-directed care for glucose and temperature control remains unknown in the United States at a time when priorities have shifted to ensure rapid diagnosis and treatment of acute stroke patients. However, protocol-driven nursing surveillance for control of hyperglycemia and hyperthermia has been shown to improve patient outcomes.Methods: We conducted an observational pilot study to assess compliance with American guidelines for glucose and temperature control and association with discharge outcomes in consecutive acute stroke patients admitted to 5 US comprehensive stroke centers. Data for the first 5 days of stroke admission were collected from electronic medical records and entered and analyzed in SPSS using descriptive statistics, Mann-Whitney U test, Student t tests, and logistic regression.Results: A total of 1669 consecutive glucose and 3782 consecutive temperature measurements were taken from a sample of 235 acute stroke patients; the sample was 87% ischemic and 13% intracerebral hemorrhage. Poor glucose control was found in 33% of patients, and the most frequent control method ordered (35%) was regular insulin sliding scale without basal dosing. Poor temperature control was noted in 10%, and 39% did not have temperature recorded in the emergency department. Lower admission National Institutes of Health Stroke Scale score and well-controlled glucose were independent predictors of favorable outcome (discharge modified Rankin Scale score, 0–2) in reperfusion patients.Conclusion: Glucose and temperature control may be overlooked in this era of rapid stroke diagnosis and treatment. Acute stroke nurses are well positioned to assume leadership of glucose and temperature monitoring and treatment.